Pertanggungjawaban Korporasi Terhadap Penyebaran Data Pribadi Nasabah Pinjaman Online Menurut Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi - Annisa Nanda Oktaviani; Fauziah Fauziah; Ade Salamah (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2025)
This research is in the background by the many cases in the community regarding the distribution of customers' personal data by online loan corporations. We need to know that sharing someone's personal data is a violation. The problem of disseminating personal data by corporations makes people feel uneasy and unsafe because of this situation. The main problem in this research is how corporate responsibility is regulated for the dissemination of personal data of online loan customers according to the Personal Data Protection Law Number 27 of 2022 and how corporate responsibility is regulated for the dissemination of personal data of online loan customers. The type of research that the author uses is normative juridical and a descriptive analytical type of approach, namely where this research describes in detail the responsibility of corporations for the dissemination of personal data, as well as knowing the sanctions imposed by the Financial Services Authority (OJK) as the authority on this matter. . Data collection techniques use interviews, questionnaires and literature study. The results of this research show that of the many cases of dissemination of personal data, not a single corporation has taken responsibility for this, there has been no compensation for customers whose personal data has been disseminated. Corporations that have committed violations are still operating as usual, corporations that have committed violations do not respond to what happens to their customers and do not have the good faith to take responsibility for their actions, and do not apologize for the violations that have been committed. Due to the lack of accountability, the public complained about this to the Financial Services Authority (OJK), the Financial Services Authority (OJK) quickly and firmly met with corporate parties who had committed violations, and the Financial Services Authority (OJK) gave administrative sanctions in the form of written warnings, restrictions on business activities, and revocation of permits in accordance with Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services.